Influence of Product Innovation, Flash Sale and Electronic Word of Mouth Regarding The Decision To Purchase Aerostreet Products on The Shopee Platform - Wibisono, Ario; Raharjo , Itot Bian (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The objective of this research is to investigate the effects of Product Innovation, Flash Sales, and Electronic Word of Mouth (e-WOM) on the purchasing decisions of Aerostreet products available on the Shopee platform. This study primarily aims to understand the influence of these three factors on consumer behavior in Indonesia's online shopping environment. Design/Method/Approach : This research adopts a quantitative methodology using surveys. A total of 40 questionnaires were administered to students from the Faculty of Economics and Business at Nusantara University PGRI Kediri. The resulting data was analyzed through multiple linear regression to assess how each independent variable affects purchasing decisions. Research Finding : The findings of the research indicate that product innovation has a positive effect on purchasing decisions, with attractive product design and quality being key factors. Flash Sales have also proven effective in increasing a sense of urgency, encouraging consumers to make impulse purchases. Additionally, e-WOM plays an important role in building consumer trust, with positive reviews from other users increasing purchasing interest. Theoretical contribution/Originality : The findings of this study offer a theoretical contribution by enhancing the understanding of the factors that affect purchasing decisions in the digital age, particularly within the e-commerce context in Indonesia. Additionally, it emphasizes the significance of Product Innovation, Flash Sales, and e-WOM in capturing consumer interest. Practitionel/Policy implication : The results of this research can be a reference for business people, especially Aerostreet, in determining more effective marketing strategies. By utilizing product innovation and Flash Sale strategies, as well as positive reviews, companies can increase their competitiveness and attract more customers on the Shopee platform. Research limitation : In this research there are several limitations, including the population which only consists of students at one university, which may not represent all Shopee users. Furthermore, the limited sample size could impact the generalizability of the findings. For future studies, it is advisable to utilize a larger and more diverse sample to achieve more comprehensive results.